Effectiveness of an Intervention Program on Nurses’ Practices toward Neonatal Intubation Suctioning Procedure at Neonatal Intensive Care Unit - Alaa Q. Ahmed, Khatam M. Hattab, (Pakistan Journal of Medical & Health Sciences, 2022)
Intubation secretion suctioning is a scientific technique carried out by intensive care nurses to keep the airway open and hence the blood oxygen saturation level within normal range. The fluid suctioning process is one of the essential procedures and priorities for nursing performance in care. Objectives: This study aimed to determine the effectiveness of an intervention program on Nurses’ practices toward neonatal intubation suctioning procedure at neonatal intensive care unit. Methodology: This is a pre-experiment design conducted on nurses working in the Intensive Care Unit at Pediatric Teaching Hospital. It started from September 30, 2021 to March 15, 2022. An observational method was adopted to collect a sample of 24 nurses to analyze the effectiveness of an intervention program on nurses' practices. A two-part checklist was developed. The validity of the instrument was determined by a committee consisting of (10) specialists from different areas. SPSS version 24.0 was used to analyze the data. Results: The results of the study showed that the neonatal intensive care unit nurses who participated in the sample numbered (24), the practices towards suctioning intubation fluids were within a low and insufficient level in the pre-test, while the post-test for all three procedures domain were within the acceptable average level. Conclusions: The study showed that there are significant differences in the impact of the program on nurses’ practices before and after implementing the program on nurses, and this indicates an improvement in the work and practices of intensive care nurses towards implementing the procedure of suctioning intubation secretion for the neonatal. Recommendation: Implementation of the interventional program for nurses’ practices and circulating to nurses in all intensive care units Designing a guidebook for the program’s steps and the steps of the procedure for withdrawing fluid from the respiratory tract of the neonatal.